Single-Domain Antibodies Efficiently Neutralize SARS-CoV-2 Variants of Concern - Favorskaya, Irina A.; Shcheblyakov, Dmitry V.; Esmagambetov, Ilias B.; Dolzhikova, Inna V.; Alekseeva, Irina A.; Korobkova, Anastasia I.; Voronina, Daria V.; Ryabova, Ekaterina I.; Derkaev, Artem A.; Kovyrshina, Anna V.; Iliukhina, Anna A.; Botikov, Andrey G.; et al. (Frontiers in Immunology, 2022)
Virus-neutralizing antibodies are one of the few treatment options for COVID-19. The evolution of SARS-CoV-2 virus has led to the emergence of virus variants with reduced sensitivity to some antibody-based therapies. The development of potent antibodies with a broad spectrum of neutralizing activity is urgently needed. Here we isolated a panel of single-domain antibodies that specifically bind to the receptor-binding domain of SARS-CoV-2 S glycoprotein. Three of the selected antibodies exhibiting most robust neutralization potency were used to generate dimeric molecules. We observed that these modifications resulted in up to a 200-fold increase in neutralizing activity. The most potent heterodimeric molecule efficiently neutralized each of SARS-CoV-2 variant of concern, including Alpha, Beta, Gamma and Delta variants. This heterodimeric molecule could be a promising drug candidate for a treatment for COVID-19 caused by virus variants of concern.